Spatial Determination of Earthquake Prone Zoning in Cugenang Sub-District - Yani, Yani; Maryani, Enok; Yani, Ahamd (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
Indonesia is one of the countries prone to earthquakes due to the importance of geological processes. Plate interactions cause seismic phenomena that have an impact on human life. This research aims to identify the factors that influence earthquakes in Cugenang District and determine earthquake-prone zones located in Cugenang District. The data is processed using a weighting system and Spatial Multi Criteria Analysis (SMCA). This overlay technique uses four parameter maps, namely rock formation maps, slope slope maps, earthquake distribution and scale maps, and geological structure maps. Making maps using geographic information system analysis and remote sensing. The main factor in the damage that occurs is due to fault movement at fine depths and the type of lithology, causing damaging vibrations. The results of the research show that Cugenang District has areas that are very high, high, medium and low prone to earthquakes. High zoning is along the fault movement path, medium category division is in areas far from the epicenter and faults, and low earthquake prone areas are very far from the epicenter and fault alignment. Making a map of earthquake-prone zoning in Cugenang District can be a recommendation for development. The government needs to carry out building code management for buildings that will be built and place buildings in zones that are safe from fault movement.